Oral hygiene after intraoral surgical interventions - Tymofeiev, Олексій Олександрович; Cherednichenko, Андрій Миколайович; Tymofeiev, Олександр Олексійович; Yaryfa, Марія Олексіївна; Chaikovskyi , Ігор Григорович (Actual Dentistry, 2024)
Purpose. Prevention of early postoperative inflammatory complications after intraoral surgical interventions. Methods. It is proposed to use modern hygiene products, 45 patients were examined after intraoral surgical interventions: 24 patients after the removal of a retained late tooth in the lower jaw and 21 patients after a sparing maxillary sinusotomy with oroantral fusion plastic surgery. Results. In the case of the recommended treatment, early inflammatory complications in the postoperative period in the form of inflammatory infiltration of soft tissues were observed in 3 of 24 patients (12.5%) after atypical tooth extraction and in 4 of 21 patients (19.1%) after sparing maxillary sinus surgery with local plastic surgery of the palate. In the control group, early postoperative complications in the form of inflammatory infiltration of soft tissues were observed in 6 out of 24 patients (25.0%) after atypical tooth extraction and in 7 patients (33.3%) after sparing maxillary sinus surgery with local palatal plastic surgery. Conclusions. Hygienic oral care using our proposed method is more effective in patients after intraoral surgical interventions compared to traditional methods of hygiene. The use of our proposed method of hygienic oral care allowed us to reduce the number of postoperative inflammatory complications by almost 2 times. We recommend using these oral hygiene products after intraoral surgical interventions. Keywords: upper jaw, lower jaw, atypical tooth extraction, sparing maxillary sinusotomy, oral hygiene, Listerine, methylene blue Ligor.